In vitro Propagation of Arbuscular Mycorrhizal Fungi May Drive Fungal Evolution - Kokkoris, Vasilis; Hart, Miranda (Frontiers in Microbiology, 2019)
Transformed root cultures (TRC) are used to mass produce Arbuscular Mycorrhizal (AM) fungal propagules in vitro. These propagules are then used in research, agriculture and ecological restoration. There are many examples from other microbial systems that long term in vitro propagation leads to domesticated strains that differ genetically and functionally. Here we discuss potential consequences of in TRC propagation on AM fungal traits, and how this may affect their functionality. We examine weather domestication of AM fungi has already happened and finally, we explore whether it is possible to overcome TRC-induced domestication.